Dechema chemistry data series : liquid - liquid equilibrium data collection 3 ternary and quaternary systems - Sorensen, J. M.; Arlt, W. (Frankfurt Dechema, 1980)
part 3
Keywords: Liquid-Liquid Equilibrium